Badania w kościele pw. Św. Apostołów Piotra i Pawła w Rąbiniu, pow. kościański. Przyczynek do studiów nad sakralną architekturą romańską w Polsce - Pawlak, Ewa; Wawrzyniak, Piotr (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
In late November and early December 2012, emergency archaeological and architectural research was carried out in the Parish Church of the Holy Apostles in Rąbiń, Kościan county. The relics of a stone Romanesque church were studied thoroughly; it is a clear-span building with a deep apse/chancel dating back to the first half of the 13th century. The subsequent phases of the church’s renovation from the 13th century until today have also been identified.